2014
DOI: 10.1159/000362246
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Epithelial Intercellular Junctional Proteins in the Sinonasal Tissue of Subjects with Chronic Rhinosinusitis: A Histopathologic Study

Abstract: Objective: To evaluate the expression of five epithelial intercellular junctional proteins in the sinonasal tissue of subjects with chronic rhinosinusitis (CRS). Methods: Forty-one samples of nasal polyp tissue of CRS patients with nasal polyps (wNP), 20 ethmoid sinus mucosa of CRS patients without nasal polyps (sNP) and 19 nasal mucosa of controls were collected and assessed for the expression of zonulae occludens (ZO-1), claudin-1, E-cadherin and desmoglein-1 and -2 (DSG1, DSG2) using immunohistochemical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Indeed, a disrupted epithelial barrier had been found in vivo and in vitro in the epithelia from patients with CRS with an altered expression pattern in TJs and this observation was more prominent in patients with CRSwNP than CRSsNP by Soyka et al . Likewise, Li et al . also reported that the expression of TJ proteins zonula occludens‐1 (ZO‐1) and claudin‐1 was significantly lower in sinonasal tissues of Chinese patients with CRSwNP compared with control subjects.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, a disrupted epithelial barrier had been found in vivo and in vitro in the epithelia from patients with CRS with an altered expression pattern in TJs and this observation was more prominent in patients with CRSwNP than CRSsNP by Soyka et al . Likewise, Li et al . also reported that the expression of TJ proteins zonula occludens‐1 (ZO‐1) and claudin‐1 was significantly lower in sinonasal tissues of Chinese patients with CRSwNP compared with control subjects.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, at the corner where three epithelial cells join, the tight junction is made up of tricellulin. It has been documented that claudin-1 and tricellulin are expressed in the epithelium of the nasal mucosa [9,10,11] as well as in the epidermis [8,12]. The epidermis contains another important barrier protein, filaggrin.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent data published in the Journal of Allergy and Clinical Immunology have reported that there is a defective epithelial barrier along with a decreased expression of TJ proteins in Western patients with CRS with nasal polyps (CRSwNP), and these defects may be mediated by cytokines IFN-g and IL-4. 2 Similarly, we have previously demonstrated that the expression of TJ proteins zonula occludens-1 (ZO-1) and claudin-1 is also significantly lower in sinonasal tissues of Chinese patients with CRSwNP compared with control subjects, 3 although the mechanisms underlying the regulation of TJ barrier integrity in these patients are not clear.…”
Section: To the Editormentioning
confidence: 99%